Estudo in silico, por dinâmica molecular clássica, da estrutura terciária da enzima MtInhA (EC 1.3.1.9) de Mycobacterium tuberculosis sob restrições da estrutura quaternária - Chitolina, Lucas Santos (2021)
Flexibility and function are related properties in the study of protein dynamics. Flexibility reflects in the conformational potential of proteins and thus in their functionalities. The presence of interactions between protein-ligands and protein-protein complexes, substrates and environmental changes, can alter protein plasticity, acting from the rearrangement of the side chains of amino acids to the unfolding/folding of large structural motifs. In order to evaluate the effects of flexibility in protein systems, we defined as the target of our work the enzyme 2-trans-enoyl-ACP (CoA) reductase of Mycobacterium tuberculosis (Mtb), or MtInhA, which presents as a homothernamer in solution. Although its quaternary structure is the biologically active form, computational studies simulate MtInhA as a monomer, justifying the independence of active sites due to their distances, as well as computational cost. However, differences in flexibility between the tetrameric and monomeric forms have already been described, which impact in the size of the enzyme binding cavity. Thus, the objective of this work was to construct a monomeric simulation model of MtInhA that presents the conformational characteristics of the quaternary structure of the enzyme. To mirror the influence of the subunits and obtain behavior similar to the protein in the native form, we applied different force constants in the monomeric structure, to restrict movement of the residues that composes the substrate binding cavity. From the comparison between monomeric systems with restrictions, tetrameric and monomer without restrictions, we observed that the simulations with force constants applied present a behavior similar to the native protein. Nevertheless, these similarities are more prominent in the A and B loops, which are important regions for modulating the flexibility of the active site. Therefore, from these results we present a monomeric simulation model of MtInhA, which has conformational characteristics of the biologically active structure. Thus, the data obtained in this work can be applied to the generation of more reliable flexible models for molecular production, and also for the performance of simulations by molecular dynamics longer and with a lower computational cost.